1999
DOI: 10.1007/s002239900650
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Laser Scanning Microscopy: A Nondestructive Subsurface Histotomography of Healthy Human Bone

Abstract: Microscopy of bony tissue usually requires special treatment for decalcification and processing of thin sections. Confocal laser scanning microscopy (CLSM) allows the nondestructive histotomography of organic hard tissue. The aim of this study was to visualize healthy human bone structures and to correlate identical areas in CLSM and conventional light microscopy. Each sample of healthy human lower jaw (n = 20) was divided into three parts: (1) fresh, untreated bony blocks studied by CLSM; (2) MMA-embedded thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…After sacrificing the animals, the implant–bone blocks were fixed in 50% ethanol and prepared for histology as described earlier (Donath & Breuner 1982) including embedding in PMMA (Technovit ® 7500; Kulzer, Hamburg, Germany). Inspection of subsurface areas of the bone/implant interface (older: boundary layer) by confocal laser scanning microscopy (CLSM) allowed the use of unsectioned and not stained block samples (Grötz et al 1999; Al‐Nawas et al 2003). Thus, the implants were cut in the mesio‐distal direction, ground to a grain of 1200 and polished.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After sacrificing the animals, the implant–bone blocks were fixed in 50% ethanol and prepared for histology as described earlier (Donath & Breuner 1982) including embedding in PMMA (Technovit ® 7500; Kulzer, Hamburg, Germany). Inspection of subsurface areas of the bone/implant interface (older: boundary layer) by confocal laser scanning microscopy (CLSM) allowed the use of unsectioned and not stained block samples (Grötz et al 1999; Al‐Nawas et al 2003). Thus, the implants were cut in the mesio‐distal direction, ground to a grain of 1200 and polished.…”
Section: Methodsmentioning
confidence: 99%
“…CLSM allows visualizing high‐contrast images of the BIC area without sectioning or staining. The method has been validated in various studies (Grötz et al 1999; Al‐Nawas et al 2003). The unstained blocks were then inspected by CLSM (Leica TCS SP2 X1: reflection mode, Leica, Wetzlar, Germany) under 633 nm laser light illumination and oil immersion objectives (× 10 magnification), resulting in an image size of 1.5 × 1.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that confocal laser scanning microscopy (CLSM) allows subsurface visualisation of nondecalcified biological hard tissue, thus reducing the problem of artefacts due to surface irregularities following the grinding process [8,9]. Being an innovative technique of histotomographic visualisation of vital osteocytes, CLSM findings have been validated by comparison of identical sample areas by standard dark field microscopy (DFM) and cell labelling with Bisbenzimide [10]. This study reports on the visualisation of the odontoblast seam by the CLSM technique and again with DFM and fluorochrome (Bisbenzimide) labelling as reference.…”
Section: Sirmentioning
confidence: 99%
“…Stepwise movement permits an artifact-free, topographic image to be obtained in a nondestructive approach without the use of special staining. 45 Stored multilayer 2D images can then be reorganized to show 3D or cross-sectional pictures. CLSM has been used for viewing the structures at the implant-tissue interface, such as unmineralized bone matrix or mineralized bone.…”
Section: Confocal Microscopymentioning
confidence: 99%